2017
DOI: 10.1177/1178221817711425
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Big Data and Twitter to Discover Emergent Online Communities of Cannabis Users

Abstract: Large shifts in medical, recreational, and illicit cannabis consumption in the United States have implications for personalizing treatment and prevention programs to a wide variety of populations. As such, considerable research has investigated clinical presentations of cannabis users in clinical and population-based samples. Studies leveraging big data, social media, and social network analysis have emerged as a promising mechanism to generate timely insights that can inform treatment and prevention research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…A growing body of literature has demonstrated that digital trace data [ 44 ] (ie, records of naturalistic digital behavior and communication) can be used to study cannabis use. For example, Twitter has been used to study new forms of cannabis administration such as dabbing [ 75 , 76 ], vaping [ 77 ], and edibles [ 78 , 79 ]; perceptions, attitudes, and normalization of cannabis use [ 80 - 82 ]; and unique communities of cannabis user subgroups and network structures of cannabis dispensaries [ 83 , 84 ]. Data from other Web-based platforms such as Reddit [ 85 ], Instagram [ 86 ], YouTube [ 87 ], and search engines such as Google [ 88 ] or Bing [ 89 ] are all other potential sources of digital trace data that have been used to study patterns of cannabis use.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…A growing body of literature has demonstrated that digital trace data [ 44 ] (ie, records of naturalistic digital behavior and communication) can be used to study cannabis use. For example, Twitter has been used to study new forms of cannabis administration such as dabbing [ 75 , 76 ], vaping [ 77 ], and edibles [ 78 , 79 ]; perceptions, attitudes, and normalization of cannabis use [ 80 - 82 ]; and unique communities of cannabis user subgroups and network structures of cannabis dispensaries [ 83 , 84 ]. Data from other Web-based platforms such as Reddit [ 85 ], Instagram [ 86 ], YouTube [ 87 ], and search engines such as Google [ 88 ] or Bing [ 89 ] are all other potential sources of digital trace data that have been used to study patterns of cannabis use.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Other clear applications of Twitter to medical research is the application of a multi-tiered approach of sentiment analysis, data-mining, and artificial intelligence to analyze tweets from the general population [ 17 , 18 ]. This real-time information can inform resource allocation for researchers and treatment plans for physicians [ 3 ].…”
Section: Current Uses Of Twitter In Healthcarementioning
confidence: 99%
“…This real-time information can inform resource allocation for researchers and treatment plans for physicians [ 3 ]. Previous studies have shown the predictive power of Twitter for public health ranging from tracking infectious disease outbreaks, natural disasters, drug use, and more [ 3 , 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. While computational power was previously a bottleneck for mining massive datasets, current advances in graphics processing units (GPUs) have enabled efficient instantaneous mining and analysis.…”
Section: Current Uses Of Twitter In Healthcarementioning
confidence: 99%
“…A growing body of literature has demonstrated that digital trace data [44] (ie, records of naturalistic digital behavior and communication) can be used to study cannabis use. For example, Twitter has been used to study new forms of cannabis administration such as dabbing [75,76], vaping [77], and edibles [78,79]; perceptions, attitudes, and normalization of cannabis use [80][81][82]; and unique communities of cannabis user subgroups and network structures of cannabis dispensaries [83,84]. Data from other Web-based platforms such as Reddit [85], Instagram [86], YouTube [87], and search engines such as Google [88] or Bing [89] are all other potential sources of digital trace data that have been used to study patterns of cannabis use.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%